2007
DOI: 10.1634/stemcells.2006-0445
|View full text |Cite
|
Sign up to set email alerts
|

Essential Alterations of Heparan Sulfate During the Differentiation of Embryonic Stem Cells to Sox1-Enhanced Green Fluorescent Protein-Expressing Neural Progenitor Cells

Abstract: Embryonic stem (ES) cells can be cultured in conditions thateither maintain pluripotency or allow differentiation to the three embryonic germ layers. Heparan sulfate (HS), a highly polymorphic glycosaminoglycan, is a critical cell surface coreceptor in embryogenesis, and in this paper we describe its structural transition from an unusually low-sulfated variant in ES cells to a more highly sulfated form in fluorescence-activated cell sorting-purified neural progenitor cells. The characteristic domain structure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
134
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 40 publications
8
134
2
Order By: Relevance
“…Recent reports have demonstrated that the HS structure changes as ESCs undergo differentiation and that specific HS epitopes appear on subpopulations of differentiated ESCs, suggesting that HS regulates ESC differentiation and cell lineage development (21,22,24). This presumption has been supported by the examination of ESCs lacking Ndst1/2 (N-deacetylase/N-sulfotransferase 1/2) or Ext1.…”
mentioning
confidence: 92%
“…Recent reports have demonstrated that the HS structure changes as ESCs undergo differentiation and that specific HS epitopes appear on subpopulations of differentiated ESCs, suggesting that HS regulates ESC differentiation and cell lineage development (21,22,24). This presumption has been supported by the examination of ESCs lacking Ndst1/2 (N-deacetylase/N-sulfotransferase 1/2) or Ext1.…”
mentioning
confidence: 92%
“…Following induction of spontaneous differentiation, Ext1 Ϫ/Ϫ ESCs showed a delay or absence of both endoderm and mesoderm markers (1). Furthermore, differentiation of Ext1 Ϫ/Ϫ ESCs into neuroectodermal precursors is defective (3). Recently, ESCs have been derived from Ext1 flox/flox embryos and following LIF withdrawal these ESCs showed a complete absence of markers of differentiation (4).…”
Section: Ext1mentioning
confidence: 99%
“…Indeed, in EXT1 or EXT2-deficient mice, On the other hand, other groups reported that EXT1-deficient ES cells, which have no HS chains, could not differentiate (36,(40)(41)(42). In the EXT1-deficient ES cells, inhibition of Nanog expression via FGF4 signaling was eliminated because FGF4 signaling, the differentiation trigger, could not work with deficient HS chains.…”
Section: The Function Of the Hs Chain In Mouse Es Cellsmentioning
confidence: 99%
“…Sulfation pattern in HS is formed by several sulfotransferases and changes during differentiation of mouse ES cells (36). This finding was achieved by phage display antibodies that recognize specific sulfation structures of HS (36,48).…”
Section: F the Function Of Sulfation Pattern Of Hs In Mouse Es Cellsmentioning
confidence: 99%
See 1 more Smart Citation